Audience Reception Analysis of Mental Health in the Movie "Ku Kira Kau Rumah" - Sari, Imas Andhita; Apriliani, Riski (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Movies are a new means of distributing entertainment that was previously customary, as well as presenting stories, music, events and many other things to the public. The role that movies play in fulfilling needs is hidden in movies. Mental health-themed films are starting to attract the attention of moviegoers. These narrative films are easy to watch because they contain a lot of new information about mental health. Ku Kira Kau Rumah, is a psychological drama film directed by Umay. In this study, researchers will be conducted with several informants from the Social Connect community. Social Connect is the largest mental health community in Indonesia. This research uses a qualitative descriptive approach. Stuart Hall's reception analysis method, there are three encoding-decoding positions described by Hall, namely dominant-hegemonic, negotiated, and oppositional which are used to find and understand the audience's meaning of the movie Ku Kira Kau Rumah. The purpose of this study is to collect very detailed data about the Social Connect Community's perception of mental health in the movie Ku Kira Kau Rumah. The data collection methods in this research are interviews, and documents. This study uses primary data and secondary data, primary data in this study are interviews, while secondary data in this study are documents, documents can be in the form of photographic scenes, in the movie Ku Kira Kau Rumah, conversations in the movie, and research. Based on the results of research conducted by researchers through in-depth interviews regarding audience reception of mental health in the film Ku Kira Kau Rumah, the audience in their acceptance is dominated by the dominant hegemonic position of the four issues studied. through the story conveyed in this film, mental health issues become the main focus that allows viewers to understand better about mental disorders, reduce stigma, and increase empathy for individuals who experience them.